Deep Listening: Transcribing Videos to Enhance Learners’ FL Listening Skills - Casañ Pitarch, Ricardo (Research in Language, 2024)
Deep listening is an educational approach that involves a high degree of concertation to decode a message. Transcribing is one of the most usual activities within this approach. This research aims to assess the efficiency of the deep listening approach among engineering degree students taking the subject of English B2. The students had to transcribe six videos in a period of twelve weeks, and their progress was measured with three listening tests that the students had to complete before, during, and after the twelve weeks. Their results were compared to those of a control group that watched the same videos. However, their exercises consisted of responding to open questions about the content of each video. Results showed that the experimental group had more significant progress than the control group, especially during the first six weeks of the experiment. In conclusion, the deep listening approach, more concretely transcription, seems to be a valuable resource for teachers that helps learners further develop their listening skills.